Pelvic Floor Muscle Training (PFMT) to Reduce Urinary Incontinence Post Radical Prostatectomy in Patients with Prostate Cancer: A Systematic Review - Dian Retno Pratiwi; Firda Yusniar; Ika Adelia Susanti; Tintin Sukartini (Jurnal Ners, 2020)
Introduction: Pelvic floor muscle training (PFMT) is an important rehabilitative approach as it plays a crucial role in the male urinary mechanism and urinary continence as well as strength. The purpose of this study was to assess the effectiveness of PFMT in the treatment of urinary incontinence post radical prostatectomy in patients with prostate cancer.Methods: Studies were systematically identified by searching electronic databases with the keywords “pelvic floor muscle training” AND “urinary incontinence” AND “radical prostatectomy” and consisted of 103 articles from Scopus, 60 articles from Science Direct, 34 articles from EBSCO, and 195 articles from Pro Quest. The data sources were limited to articles published from 2011 to 2020 and those published in English.Results: Fifteen studies were included in this systematic review with inclusion criteria being patients diagnosed with prostate cancer, men with urinary incontinence after radical prostatectomy, types of study: Randomized Controlled Study (RCT) and protocol study, intervention: PFMT and main outcome: continence rate. Twelve of fifteen articles suggest PFMT is significantly more effective than the standard care in improving recovery of continence in patients undergoing radical prostatectomy.Conclusion: PFMT is effectively carried out with a duration of 10-45 minutes per day with 10 contractions in a lying, sitting, and standing position with three sets, time of contractions 5-10 seconds and relaxation 5-10 seconds. The benefits of this review are that PFMT is suitable, well accepted and achievable for the patients who experience incontinence after radical prostatectomy.